ANEKA MANFAAT PENGGUNAAN KOMPOS CAIR (LARUTAN DRANCO) BASIL PROSES FERMENTASI ANAEROBIK DENGAN BAHAN BAKU SAMPAH KOTA - R Sudradjat (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
Dranco (Dry Anaerobic Conversion) process is anaerobic fermentation to produce biogas and paste residue. Through pressing, the residue will yield solid compost (humotex) and liquid compost (Dranco liquid). The aim of this inveatigation is to know the effect of the utilization of dranco liquid when applying it as compost either the effect on soil or plant.The results showed that Dranco liquid contained very low P. Ca, Mg, Fe, Mn. Zn and heavy metals Kj-N, K and Na were also low but high enough when comparing with other nutrients in Dranco liquid. The NH4+ was ranked as high.Addition of Dronco liquid brought about an increase of E.C 3 - 6 times depends on soil types ,and liquid concen- trotion, while soil pH increased 1.5 - 2 level. The highest growth of maize was achieved when soil was mixed with Dranco liquid that was diluted 2 - 10 times. Besides, addition of Draneo liquid can maintain the life of maize plant under water lacking condition. Addition of Drenco liquid increased soil agregate stability 2 - 2 0 times depends on soil types and Dranco liquid concentration. Nitrification process was able to convert NH4+ in the Dranco liquid to N03- with an efficicncy capacity of 35 %. As a conclusion, Dranco liquid is useful to be used as compost liquid for increasing soil fertility as well as promoting plant growth.